A comparison between large‐scale irregularities and scintillations in the polar ionosphere. Issue 10 (27th May 2016) - Wang, Y.; Zhang, Q.‐H.; Jayachandran, P. T.; Lockwood, M.; Zhang, S.‐R.; Moen, J.; Xing, Z.‐Y.; Ma, Y.‐Z.; Lester, M.
Abstract: A comparison tool has been developed by mapping the global GPS total electron content (TEC) and large coverage of ionospheric scintillations together on the geomagnetic latitude/magnetic local time coordinates. Using this tool, a comparison between large‐scale ionospheric irregularities and scintillations is pursued during a geomagnetic storm. Irregularities, such as storm enhanced density, middle‐latitude trough, and polar cap patches, are clearly identified from the TEC maps. At the edges of these irregularities, clear scintillations appeared but their behaviors were different. Phase scintillations ( σφ ) were almost always larger than amplitude scintillations ( S 4 ) at the edges of these irregularities, associated with bursty flows or flow reversals with large density gradients. An unexpected scintillation feature appeared inside the modeled auroral oval where S 4 were much larger than σφ, most likely caused by particle precipitations around the exiting polar cap patches. Key Points: A comparison tool has been developed by mapping global GPS TEC and large coverage of scintillations together on MLAT/MLT coordinates σφ were larger than S 4 at the edges of the irregularities associated with bursty flows or flow reversals with large density gradients S 4 were much larger than σφ in the auroral oval, most likely caused by particle precipitations around the exiting polar cap patches